Melioidosis in lower provincial Cambodia: A case series from a prospective study of sepsis in Takeo Province. - Kevin L Schully; Catherine M Berjohn; Angela M Prouty; Amitha Fitkariwala; Tin Som; Darith Sieng; Michael J Gregory; Andrew Vaughn; Sim Kheng; Vantha Te; Christopher A Duplessis; James V Lawler; et al. (Public Library of Science (PLoS), 2017)
Melioidosis is a severe infectious disease caused by the gram-negative soil bacterium Burkholderia pseudomallei. Melioidosis is well known to be a major cause of morbidity and mortality in Southeast Asia, particularly in Thailand. However, melioidosis remains underreported in surrounding areas such as Cambodia. We report a case series of melioidosis in seven patients from Takeo Province, Cambodia. The patients, aged 24-65 years, were enrolled from May 2014 to May 2015 during a one year prospective study of sepsis at Takeo Provincial Hospital. They presented with fever, rigors, dyspnea, fatigue, diaphoresis, productive cough, and skin abscesses. Six of the seven patients were also hyponatremic. B. pseudomallei was cultured from the blood of six patients and the sputum of one patient. In this manuscript, we provide a detailed description of the clinical presentation, case management and laboratory confirmation of B. pseudomallei, as well as discuss the difficulties of identifying and treating melioidosis in low resource settings.